SIMULATION AND EXPERIMENTAL INVESTIGATION OF WRINKLE DEFECT IN DEEP DRAWING PROCESS OF CARBON STEEL SPCC SHAPED CYLINDER FLANGE CUP - Bambang Mulyanto; Deni Shidqi Khaerudini (Universitas Mercu Buana, 2020)
A Sheet Metal Forming (SMF) process, especially deep drawing, is one of the manufacturing processes that commonly used in the automotive industry. Compared with casting and forging, the SMF process has several advantages, including lesser weight materials and broader variations in shape that can be made. One of the problems in the SMF process is the wrinkling phenomenon, which can cause the size and appearance defects of sheet products. The wrinkle occurs because of the mechanical properties of the material, product geometry, and blank holder force (BHF). Several variations of BHF were applied in these simulations and experiments to eliminate the wrinkle defects of cylinder flange cup test products. The characteristic of the cylinder flange cup is from the cold-rolled coiled steel plate (SPCC) type of material with a thickness of 0.8 and 1.0 mm, the height of 10 mm, the inner diameter of 58 mm, and flange diameter of 76 mm. Simple simulations of the SMF process were carried out by using Solidworks with version 2017, and the experiment was carried out at a 600 kN press with a punch velocity of 40 strokes per minute and blank holder force variations from 0 to 21 kN. The experimental data performed with a single die on a flanged cup cylindrical test material shows that the higher the blank holder force (BHF) number, the smaller the wrinkle defect, and it can be eliminated starting from the BHF number of 15 kN.